Fully reversible lithium storage of tin oxide enabled by self-doping and partial amorphization. Issue 27 (28th June 2019) - Pang, Yuepeng; Wang, Jing; Yang, Junhe; Fang, Fang; Sun, Dalin; Zheng, Shiyou
Abstract : Self-doping and partial amorphization lead to a full reversibility of SnO2 by suppressing the agglomeration of Sn during cycling. Abstract : SnO2 has a high theoretical capacity of 1493 mA h g −1 as an anode material for Li-ion batteries, but its full reversibility is difficult to achieve upon cycling due to the sluggish kinetics. We for the first time demonstrate a fully reversible SnO2 anode for Li-ion batteries enabled by self-doping and partial amorphization by anchoring its nanoparticles on a graphene/single walled carbon nanotube hybrid framework. The uniquely structured nanocomposite containing 74% SnO2 exhibits high reversible capacities together with good rate and cycling capabilities. For instance, the composite anode retains an overall capacity of 1215 mA h g −1 (1425 mA h g −1 for SnO2 ) after 200 cycles at 0.1 A g −1, which is very close to its theoretical capacity. Moreover, an overall capacity of 947 mA h g −1 (1062 mA h g −1 for SnO2 ) can be delivered at a higher rate (1 A g −1 ) with 98% capacity retention over 350 cycles. This exceptional performance can be attributed to the formation of highly dispersed metallic Sn in the Li2 O matrix during cycling, which is caused by the unique two-step lithiation mechanism of the self-doped and partially amorphous SnO2 nanoparticles. A similar strategy can also be applied to develop other high-performance electrodes with conversion reactions.